THE EFFECT OF LOCAL ORIGINAL REVENUE (PAD) AND TRANSFER FUNDS ON REGIONAL EXPENDITURE: A FLYPAPER EFFECT ANALYSIS OF REGENCY/CITY IN NORTH SUMATERA PROVINCE - Juliana Siahaan; Abdillah Arif Nasution; Ibnu Austrindanney Sina Azhar (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
Fiscal decentralization grants regional governments greater authority to manage their own revenues and expenditures, yet many local governments in Indonesia remain heavily dependent on central government transfers rather than own-source revenue (PAD). This dependency raises the possibility of a flypaper effect, a condition in which regional expenditure responds more strongly to transfer funds than to PAD. This study examines the influence of PAD and transfer funds on capital expenditure and routine expenditure, and tests for the presence of a flypaper effect, among regency and municipal governments in North Sumatra Province. Using an explanatory quantitative approach, the study analyzes panel data from 33 regencies and cities over the 2019–2024 period (198 observations), drawn from official BPS and DJPK publications, with gross regional domestic product and population included as control variables. Panel regression results show that both PAD and transfer funds have a positive and significant effect on capital expenditure and on routine expenditure. In both expenditure models, however, the coefficient of transfer funds exceeds that of PAD, indicating that regional expenditure is more responsive to central transfers than to locally generated revenue. The findings confirm the presence of a flypaper effect among North Sumatra's regency and city governments and underscore the need to strengthen local revenue mobilization to support genuine fiscal independence.